2022
DOI: 10.3390/ijms23169361
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Nanoparticles: Promising Treatment Approach for Parkinson’s Disease

Abstract: Parkinson’s disease (PD), a neurodegenerative disorder, is a life-altering, debilitating disease exhibiting a severe physical, psychological, and financial burden on patients. Globally, approximately 7–10 million people are afflicted with this disease, with the number of cases estimated to increase to 12.9 million by 2040. PD is a progressive movement disorder with nonmotor symptoms, including insomnia, depression, anxiety, and anosmia. While current therapeutics are available to PD patients, this treatment re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
5

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 95 publications
0
15
0
5
Order By: Relevance
“…Similarly, NLCs are modified SLNs in which the lipid phase consists of liquid lipids (oils) and solids at room temperature . The small size and lipid nature of SLNs and NLCs facilitate crossing the BBB, especially in the leaky tumor vasculature. , Regarding drug delivery to the CNS, both SLNs and NLCs have been confirmed to improve the treatment of several neurological diseases, such as Parkinson’s disease, Alzheimer’s disease, migraine, epilepsy, and brain cancer . Many studies demonstrated the superiority of NLCs and SLNs over other nanoparticles (e.g., PLGA NPs) to promote targeted delivery of drugs to the brain due to their lipid properties. …”
Section: Permeation Mechanisms Of Nanoparticles Capable Of Crossing T...mentioning
confidence: 99%
“…Similarly, NLCs are modified SLNs in which the lipid phase consists of liquid lipids (oils) and solids at room temperature . The small size and lipid nature of SLNs and NLCs facilitate crossing the BBB, especially in the leaky tumor vasculature. , Regarding drug delivery to the CNS, both SLNs and NLCs have been confirmed to improve the treatment of several neurological diseases, such as Parkinson’s disease, Alzheimer’s disease, migraine, epilepsy, and brain cancer . Many studies demonstrated the superiority of NLCs and SLNs over other nanoparticles (e.g., PLGA NPs) to promote targeted delivery of drugs to the brain due to their lipid properties. …”
Section: Permeation Mechanisms Of Nanoparticles Capable Of Crossing T...mentioning
confidence: 99%
“…65,69,70 Nanomedicine is the utilization of various nanoplatforms toward health and medicine, specifically regarding the treatment and diagnosis of diseases. 71 Nanoplatforms have revolutionized drug delivery, as their unique features allow therapeutic agents to selectively target organs, tissues, and cells while minimizing the exposure of healthy tissues to these therapeutic agents. 72,73 These features include the ability to modify their surface layer with ligands, antibodies, cations, and other surface modifiers that target specific organelles/organs.…”
Section: Nanoplatforms and Nanomedicinementioning
confidence: 99%
“…HHEren izaera babesleak molekula terapeutikoen garunerako sarrera mugatu eta PGrako farmako eraginkorren diseinua zailtzen du [8,12]. Horregatik, interes zientifikoa farmakoek HHE gurutzatzeko estrategia desberdinak garatzean oinarritzen da egun [8,11].…”
Section: Sarreraunclassified